TELA’AH HUKUM ISLAM TERHADAP PERILAKU SEKS ANAK DI BAWAH UMUR DI KOTA MAKASSAR - Gunawan, Budi MR; Idrus, Achmad Musyahid (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2020)
This article discusses the role of Islamic legal views on the free sex of minors. The main problem is that the most influential factor in changing adolescent behavior in free sex is the entry of western culture to developing countries like Indonesia, one of which is in the Bara-Barayya Makassar village. The authors formulate the following sub-problems: 1. What are the factors Causes of free sex underage children? 2. How are efforts to control free sex among minors? 3. Islamic legal theory regarding the free sex of minors.The type of research used is field research (Field Research) which is descriptive qualitative. Primary data sources are through interviews. This research contains secondary data sources of analysis through books, statutory regulations, and related theses. The approach used is juridical. and Syar'i. Furthermore, the data collection methods used are observation, interview, and documentation. Then, data processing techniques and data analysis were carried out through three stages, namely: data editing, data coding, and data analysis.The results of this study indicate that: 1) Free sex in the city of Makassar, especially underage children in the Bara-Barayya village, still really needs to do a social, religious, and direct touch from the family because the family is the place for the child's first socialization. 2) The social environment in-community and school are places of direct contact for children in socializing themselves, therefore it is necessary to strengthen understanding of religion and the foundation of self-strengthening before going directly to the community. 3) The habit of watching pornographic films and dating can lead to child-free sexual behavior.The implication of the research is that the Makassar City government or all related agencies and agencies and the surrounding community need to carry out several approach programs for minors, in this case, the sex of minors, including the need to synergize existing programs in government and in the community.